2017
DOI: 10.1155/2017/8208261
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Herbal Medicines as Potential Agents for Alleviation of Heat Stress in Poultry

Abstract: Heat stress negatively affects the productivity of chickens in commercial poultry farms in humid tropics. In this study, the concentrations and types of the antioxidant compounds of eight Chinese herbal medicines, which have previously demonstrated promising effects on suppressing heat stress as a mixture, were investigated using reversed-phase High Performance Liquid Chromatography, spectrophotometry, Liquid Chromatography Mass Spectrometry, and Gas-Liquid Chromatography. Our results provided the levels of ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The ban on commercial antibiotics usage in the animal industry causes researchers to develop alternate feed supplements. Recently, feed additives such as amino acids, trace elements, and vitamins (1)(2)(3), as well as probiotics, polyphenols, and flavonoid have been utilized to maximize poultry immunity and productivity (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…The ban on commercial antibiotics usage in the animal industry causes researchers to develop alternate feed supplements. Recently, feed additives such as amino acids, trace elements, and vitamins (1)(2)(3), as well as probiotics, polyphenols, and flavonoid have been utilized to maximize poultry immunity and productivity (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Some authors (Shokryazdan et al, 2017) mentioned that inulin is prebiotic that can be absorbed by liver and colon cells and can act as an antioxidant. Other studies, showed that in normal raising conditions, inulin was very effective on enhancing intestinal immune function (Huang et al, 2015), and recently was reported that inulin can replace antibiotics as growth promoters without affecting the physicochemical characteristics of meat (Guaragni et al, 2020;.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, herbs are natural medicinal plants, and the plant extracts produce no drug synthetic compound residues in tissues and exhibit anti-bacterial and anti-inflammatory properties [ 3 , 4 , 5 ], which have proved to be effective in the search for alternatives to antibiotics [ 6 , 7 ]. The specific Compound Chinese Herbal Medicine Additive (CCHMA) used in this study consisted of Astragalus , Licorice , Radix Codonopsis , Citri Reticulatae Pericarpium , Angelica Sinensis , Atractylodis and Cimicfugae Rhizoma in the ratio of 6:6:4:3:3:1:1.…”
Section: Introductionmentioning
confidence: 99%